2015
DOI: 10.1063/1.4921038
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate energy electron impact excitation of composite vibrational modes in phenol

Abstract: Absolute cross sections for vibrational excitations of cytosine by low energy electron impact J. Chem. Phys. 137, 115103 (2012) We report differential cross section results from an experimental investigation into the electron impact excitation of a number of the low-lying composite (unresolved) vibrational modes in phenol (C 6 H 5 OH). The measurements were carried out at incident electron energies in the range 15-40 eV and for scattered-electron angles in the range 10-90• . The energy resolution of those meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…3 We were therefore interested to see how those physico-chemical properties manifested themselves, if at all, in the behaviour of the measured composite vibrational-mode and/or electronic-state excitation ICSs. In addition, Neves et al 21 found some evidence for a higher-lying shape resonance enhancing the phenol cross sections vis à vis those of benzene. Support for the existence of that resonance was also found in our Schwinger Multichannel Method with Pseudo-potentials (SMCPP) calculations for the elastic channel 20 and our experimental total cross section measurements.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 We were therefore interested to see how those physico-chemical properties manifested themselves, if at all, in the behaviour of the measured composite vibrational-mode and/or electronic-state excitation ICSs. In addition, Neves et al 21 found some evidence for a higher-lying shape resonance enhancing the phenol cross sections vis à vis those of benzene. Support for the existence of that resonance was also found in our Schwinger Multichannel Method with Pseudo-potentials (SMCPP) calculations for the elastic channel 20 and our experimental total cross section measurements.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we have conducted a series of joint experimental and theoretical studies looking at the behaviour of electron-phenol scattering processes. Specifically, results for phenol's (e, 2e) triple differential cross sections (DCSs), 19 elastic scattering and total cross sections (TCS), 20 vibrational excitation differential cross sections, 21 and excited electronic-state differential cross sections 22 have all thus far been reported. In addition, a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations